Transitional Cell Carcinoma within a Portion of Inguinally Herniated Bladder - Uhlman, Matthew A. (Hindawi Publishing Corporation, 2013)
Bladder herniation within the inguinal canal is a relatively uncommon finding. We report an even less-common occurrence of transitional cell carcinoma located within a portion of inguinally herniated bladder. Fewer than 20 reports exist in the literature describing this scenario.